The Use of Artificial Intelligence (AI) in Teaching English Writing - Atikah, Atikah (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
This study investigates the use of Artificial Intelligence (AI) in english language teaching. It examines the integration of AI in learning english writing skills. The research employs a library research method by reviewing relevant books, articles, and previous studies related to AI in language learning. The findings reveal that AI can create a supportive and interactive environment for learning English by providing personalized feedback, adaptive learning opportunities, and increased access to learning resources. AI-powered tools are able to assist learners in improving grammar accuracy, vocabulary choice, sentence structure, paragraph organization, and overall writing quality. In addition, these technologies help students generate ideas, revise drafts, and build confidence during the writing process. Therefore, the integration of AI in teaching English writing can be considered an innovative approach to improving the effectiveness of the learning process and enhancing students’ writing achievement.